A SYSTEMATIC LITERATURE REVIEW ON MEDIA TECHNOLOGY IN CREATIVE THINKING FOR ELEMENTARY SCHOOL STUDENTS - Lestari, Ika; Nurbaeti, Meli; Wahyudiana, Endang (PARAMETER: Jurnal Pendidikan Universitas Negeri Jakarta, 2022)
Creative thinking is one of the thinking abilities of students in solving problems in the process of learning activities. This study aims to 1) identify creative thinking skills performed by elementary school students; 2) identify factors that influence creative thinking skills in elementary schools in the digital era; 3) to analyze the implementation of creative thinking methods or techniques given to elementary school students; 4) analyze publication articles (objectives, methods, and research results) in scientific journals in 2010-2022 related to the creative thinking skills of elementary school students. This research uses a systematic literature review method with all articles found and processed based on the criteria of inclusion, exclusion, quality assessment which is then found as many as 25 articles analyzed in accordance with the questions that have been set. The results of the study are in the form of an overview of creative thinking that has been widely discussed by previous studies including influential factors in creative thinking, methods or techniques used and research trends during the period 2010-2022. This research has implications for the discovery of future research that can be used as an initial foothold for future researchers who have an interest in the theme of research on creative thinking skills in students. Abstrak Berpikir kreatif salah satu kemampuan berpikir siswa dalam menyelesaikan masalah didalam proses kegiatan belajar. Penelitian ini bertujuan 1) mengidentifikasi keterampilan berpikir kreatif yang dilakukan oleh siswa sekolah dasar; 2) mengidentifikasi faktor-faktor yang berpengaruh kemampuan berpikir kreatif di sekolah dasar pada era digital; 3) untuk menganalisis pelaksanaan dari metode atau teknik kemampuan berpikirkreatif yang diberikan ke siswa sekolah dasar; 4) menganalisis artikel publikasi (tujuan, metode, dan hasil penelitian) dalam jurnal ilmiah tahun 2010-2022 berkaitan dengan kemampuan berpikir kreatif siswa sekolah dasar. Penenlitian ini menggunakan metode systematic literature review dengan seluruh artikel yang ditemukan dan diolah berdasarkan kriteria inklusi, eksklusi, quality assesment yang kemudian ditemukan sebanyak 25 artikel dianalisis sesuai dengan pertanyaan yang telah ditetapkan. Hasil penelitian berupa gambaran berupa berpikir kreatif yang selama ini banyak dibahas oleh penelitian terdahulu termasuk faktor-faktor yang berpengaruh dalam berpikir kreatif, metode atau teknik yang digunakan dan kecenderungan penelitian selama kurun waktu tahun 2010-2022. Penenlitian ini berimpilkasi pada ditemukannya penelitian berikutnya yang dapat dijadikan sebagai pijakan awal para peneliti berikutnya yang memiliki ketertarikan dalam tema penelitian tentang kemampuan berpikir kreatif pada siswa.